Assessment of gait deviation on the Babinski-Weill test in healthy Brazilians - Camila Souza Miranda; Camila Piccirilli Stefani; Marcia Midori Morimoto; Maria Elisa Pimentel Piemonte; Cristiana Borges Pereira (Arquivos de Neuro-Psiquiatria)
Objective The aim of this study was to validate a simple and reproducible method for assessing gait deviation on the Babinski-Weill test in a representative sample of healthy Brazilians. Methods Gait deviations were measured in 75 individuals (median=30 years, 41 women) for forward, backwards, and Babinski-Weill steps. The test entailed blindfolded individuals walking 10 paces at a frequency of 1 Hz with deviations subsequently measured by a protractor. Results Mean gait deviation forward was 0.53° with standard deviation (SD)=4.22 and backwards was 2.14° with SD=4.29. No significant difference in deviation was detected between genders (t test p=0.40 forward and p=0.77 backwards) or for age (ANOVA, p=0.33 forward and p=0.63 backwards). On the Babinski-Weill test, mean gait deviation was 5.26°; SD=16.32 in women and -3.11°; SD=12.41 in men, with no significant difference between genders (t test, p=0.056). Discussion Defining normative gait patterns helps distinguish pathological states.